2021
DOI: 10.1186/s12974-021-02364-z
|View full text |Cite
|
Sign up to set email alerts
|

Circulating extracellular vesicles activate the pyroptosis pathway in the brain following ventilation-induced lung injury

Abstract: Background Mechanical ventilation of preterm newborns causes lung injury and is associated with poor neurodevelopmental outcomes. However, the mechanistic links between ventilation-induced lung injury (VILI) and brain injury is not well defined. Since circulating extracellular vesicles (EVs) are known to link distant organs by transferring their cargos, we hypothesized that EVs mediate inflammatory brain injury associated with VILI. Methods Neonata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
(40 reference statements)
2
11
0
Order By: Relevance
“…Many studies have demonstrated a critical role for GSDMD in regulating pyroptosis and inflammation in various adult diseases. However, there are no reports on the role of GSDMD in neonatal lung and retinal injury in preterm infants, but recent studies from our laboratory have highlighted a critical role for GSDMD in hyperoxia-indued and mechanical ventilation-associated neonatal lung and brain injury in rodent models 15 , 16 . We showed that GSDMD is activated by hyperoxia in the lungs and brains of neonatal mice and that treatment with a pharmacological inhibitor of GSDMD attenuated hyperoxia-induced BPD-like pathology and brain injury 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated a critical role for GSDMD in regulating pyroptosis and inflammation in various adult diseases. However, there are no reports on the role of GSDMD in neonatal lung and retinal injury in preterm infants, but recent studies from our laboratory have highlighted a critical role for GSDMD in hyperoxia-indued and mechanical ventilation-associated neonatal lung and brain injury in rodent models 15 , 16 . We showed that GSDMD is activated by hyperoxia in the lungs and brains of neonatal mice and that treatment with a pharmacological inhibitor of GSDMD attenuated hyperoxia-induced BPD-like pathology and brain injury 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Injection of these EVs aggravates neuroinflammation by activating glial cells and the NF-κB signaling pathway and releasing pro-inflammatory cytokines ( 186 ). Circulating EVs from ALI lead to the activation of microglia and the pyroptosis pathway, which worsen neuroinflammation ( 156 ). Collectively, these studies show that circulating EVs play a crucial role in neuroinflammation.…”
Section: Diverse Cell-derived Extracellular Vesicles and Neuroinflamm...mentioning
confidence: 99%
“…Intestinal epithelial cells have been reported to release EVs to induce IL-1β-mediated neuronal injury in sepsis-associated encephalopathy, which launches long-term cognitive deficits and neurodegeneration [ 163 ]. Moreover, ventilation-induced lung injury causes lung inflammation, leading to selective loading of caspase-1 into lung-derived EVs [ 164 ]. Caspase-1-enriched peripheral EVs induce microglial activation and cell pyroptosis in the brain, revealing circulating EVs as a pathogenic factor of NDs [ 164 ].…”
Section: Pathological Roles Of Evs In Ndsmentioning
confidence: 99%
“…Moreover, ventilation-induced lung injury causes lung inflammation, leading to selective loading of caspase-1 into lung-derived EVs [ 164 ]. Caspase-1-enriched peripheral EVs induce microglial activation and cell pyroptosis in the brain, revealing circulating EVs as a pathogenic factor of NDs [ 164 ].…”
Section: Pathological Roles Of Evs In Ndsmentioning
confidence: 99%